Calreticulin mutation analysis in non-mutated Janus kinase 2 essential thrombocythemia patients in Chiang Mai University: analysis of three methods and clinical correlations - Ekarat Rattarittamrong (2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group Objectives: The primary objective was to determine the prevalence of calreticulin (CALR) mutation in patients with non-JAK2V617F mutated essential thrombocythemia (ET). The secondary objectives were to evaluate the accuracy of CALR mutation analysis by high-resolution melting (HRM) analysis and real-time polymerase chain reaction (PCR) compared with DNA sequencing and to compare clinical characteristics of CALR mutated and JAK2V617F mutated ET. Methods: This was a prospective cohort study involving ET patients registered at Chiang Mai University in the period September 2015–September 2017 who were aged more than 2 years, and did not harbor JAK2V617F mutation. The presence of CALR mutation was established by DNA sequencing, HRM, and real-time PCR for type 1 and type 2 mutation. Clinical data were compared with that from ET patients with mutated JAK2V617F. Results: Twenty-eight patients were enrolled onto the study. CALR mutations were found in 10 patients (35.7%). Three patients had type 1 mutation, 5 patients had type 2 mutation, 1 patient had type 18 mutation, and 1 patients had novel mutations (c.1093 C–G, c.1098_1131 del, c.1135 G–A). HRM could differentiate between the types of mutation in complete agreement with DNA sequencing. Patients with a CALR mutation showed a significantly greater male predominance and had a higher platelet count when compared with 42 JAK2V617F patients. Discussion and Conclusions: The prevalence of CALR mutation in JAK2V617F-negative ET in this study is 35.7%. HRM is an effective method of detecting CALR mutation and is a more advantageous method of screening for CALR mutation.